Induction of genetic variation and variability of Saudi Arabian cultivars of wheat - Algwaiz, Hussah I. (International Journal of Environment, Agriculture and Biotechnology, 2021)
This study was undertaken to explore the possibility of inducing micromutations in quantitative traits and meiotic anomalies of bread wheat (T. aestivum L.) after irradiated dry and soaked seeds with 0.0, 0.5, 5 and 10 Krad of gamma rays. Traits (number of spikes per plant, number of grains per spike, number of spikelets per spike, spike density, grain yield per plant, weight of grain yield per plant and weight of 1000-grain per plant) were analyzed quantitatively to assess the extent of the variation in M1 and M2 generations. At the same time, the number of economical traits (heading date, plant height, number of tillers per plant, average of spike length, total protein percent and wet and dry gluten percent) were also investigated. Results showed that all quantitative traits varied significantly in M1 and M2 at doses rather than seed condition. Specific action of dose 0.5 Krad showed significant increase for some traits for three lines in M1 and M2, and the magnitude and direction for number of spikes per plant, grain yield per plant and weight of grain per plant was significant for all three lines at treatments. There was a considerable increase in genotypic variance, heritability and genetic advance indicating the effectiveness of gamma doses in inducing polygenic mutation. The treatment with different doses caused a highly significant increase in abnormal cells, while pollen fertility percent decreased with increasing gamma ray doses. M1 and M2 irradiated generations showed presence of significant differences at doses rather than seed conditions. A 5 Krad dose showed a significant increase in some traits for dry and soaked seeds for three lines at <1 and M2 generations. There was also a considerable increase in genotypic variance, heritability and genetic advance for some traits. Radiation was shown to change the degree of association between traits.